2016
DOI: 10.1590/0103-8478cr20141648
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater use in agriculture and potential effects on meso and macrofauna soil

Abstract: The use of wastewater in agriculture has been practiced on an increasing scale over the past decades because of its fertilizing potential and the reduction in demand for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
(15 reference statements)
0
11
0
1
Order By: Relevance
“…Several studies have reported the impact of wastewater disposal on soil Rosa et al, 2017), leachate (Prior et al, 2009;Maggi et al, 2011;Lourenzi et al, 2014b), drained (Dal Bosco et al, 2008b;Doblinski et al, 2010;Wang et al, 2013), crops (Kessler et al, 2013a;Kessler et al, 2013b;Passarin et al, 2016;Lourenzi et al, 2014a), and biota (Tessaro et al, 2013;Brooks et al, 2014;Castaldelli et al, 2015;Tessaro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the impact of wastewater disposal on soil Rosa et al, 2017), leachate (Prior et al, 2009;Maggi et al, 2011;Lourenzi et al, 2014b), drained (Dal Bosco et al, 2008b;Doblinski et al, 2010;Wang et al, 2013), crops (Kessler et al, 2013a;Kessler et al, 2013b;Passarin et al, 2016;Lourenzi et al, 2014a), and biota (Tessaro et al, 2013;Brooks et al, 2014;Castaldelli et al, 2015;Tessaro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Atıksuların tarımsal sulamada tekrar kullanılmasının amacı sulama için gerekli su ihtiyacını karşılamak bu sırada da hem çevreyi oluşabilecek olumsuz etkilere karşı korumak hem de üretici ve tüketicilerin sağlık güvenliğini sağlamaktır [28]. Ayrıca kentsel atıksular ile tarım arazilerinin uzun dönem sulanması toprağın kimyasal bileşimi, morfolojisi ve fiziksel yapısı gibi kalite özelliklerini bozabilmekte ve yeraltı suyunu kirletebilmektedir [2], [29], [30]. Bu nedenle arıtılmış atıksular ile sulamanın yapılacağı alanlarda iyi bir drenaj sisteminin yapılması ve zamanla birikecek kirleticilerin yıkanarak bu drenaj sistemleri vasıtasıyla topraktan uzaklaştırılması gerekmektedir.…”
Section: Atıksuların Tarımsal Sulamada Kullanılmasında öNemli Parametrelerunclassified
“…Another contributing factor is the change in soil physical and chemical characteristics caused by periodic SW application (TESSARO et al, 2016). Between both soybean crops, two SW applications were carried out in the sample area for corn and black oat cultivation, respectively.…”
Section: Pca Of Ecological Indices Of Each Treatment Is Shown Inmentioning
confidence: 99%
“…Soil chemical changes are directly influenced by microbiological activity and soil meso-and macrofauna, which can be changed by the addition of organic effluents as a function of food supply, temperature modification, and soil cover (MOURA et al, 2016;TESSARO et al, 2016). The effects on soil fauna can be positive or negative, varying according to residue composition and management, which are capable of altering the quality and quantity of soil organic matter, the C/N ratio, and metal accumulation such as copper and zinc present in high amounts in swine residues (POSTMA-BLAAUW et al, 2012).…”
Section: Introductionmentioning
confidence: 99%